Prevalence of caries in Brazilian children with cleft lip andor palate, aged 6 to 36 months - Agda Maria de Moura; Marcia Andre; Margareth Torrecillas Lopez; Reinaldo Brito e Dias (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The aim of this study was to assess the prevalence of caries in children with cleft lip and∕or palate aged 6-36 months of life. This study was conducted at the University of São Paulo School of Dentistry, Brazil. A total of 143 children were selected (73 male, 70 female), all of whom had at least two erupted teeth. The children were distributed as follows: 88 had cleft lip and palate, 35 had cleft palate, 20 had cleft lip. Dental caries disease was diagnosed according to criteria set by the World Health Organization. It was observed that 18.9% of the study children had caries. No correlation between prevalence of caries and gender or type of cleft was observed. Mean dmf-t was 0.47. The prevalence of caries was higher in the upper arch, and the most affected tooth was the central incisor (p = 0.001). Children with cleft lip and∕or palate did not have high caries indices.